Biosynthesis of Silver Nanoparticles Using Black Pepper (Piper nigrum L.) Essential Oil as a Bioreductor - Erliyanti, Nove Kartika; Wira, Guardiola Rosa; Maharani, Hijria Putri; Pujiastuti, Caecilia; Panjaitan, Renova (Jurnal Rekayasa Kimia & Lingkungan, 2025)
The development of environmentally friendly methods for nanoparticle synthesis has gained increasing attention. Black pepper essential oil contains secondary metabolites that act as both reducing and stabilizing agents, making it a promising green alternative in silver nanoparticle (AgNP) synthesis. This study aims to investigate the effect of pH and synthesis time on the yield and characteristics of AgNP synthesized using black pepper essential oil via the sonochemical method. AgNP synthesis was carried out using the sonochemical method by adding black pepper essential oil to a silver nitrate solution. AgNP were synthesized at pH levels of 8, 9, and 10 with reaction times of 30, 60, and 90 minutes. The obtained AgNP were analyzed for yield, UV-Vis absorbance, and particle size distribution. The results demonstrated that yield increased with higher pH and longer synthesis time, reaching a maximum of 58.12% at pH 10 and 90 minutes. UV-Vis analysis confirmed the presence of AgNP with absorption peaks between 400500 nm. The particle size ranged from 9.66 to 348 nm, indicating size variability influenced by synthesis conditions. These findings highlight the potential of black pepper essential oil as a green and sustainable approach for AgNP synthesis, offering eco-friendly benefits for various applications.